THE RELATIONSHIP BETWEEN THE TALKING STICK METHOD WITH STUDENT'S MOTIVATION TO STUDY (Survey on Akidah Akhlak Subjects at MTs Nurul Islam Bekasi) - Sutiono Sutiono; Aprilia Damayanti (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
The low learning motivation of students can be shown by the lack of student activity in participating in learning. Student inactivity in the learning process can include not paying attention to the lesson, not asking the teacher about material that is not clear, and not answering questions from the teacher. Learning motivation is the driving force in students that causes learning activities, which ensure the continuity of learning activities and which provide direction to learning activities so that the goals desired by students in learning can be achieved. This study aims to determine the effect of the talking stick method on the learning motivation of eighth grade students at MTs Nurul Islam Bekasi. The sample size is all students of class VIII MTs Nurul Islam Bekasi, totaling 64 people. The research method used is descriptive correlational.The results showed that: 1) the use of the talking stick method in Akidah Akhlak subjects at MTs Nurul Islam Bekasi was quite effective (good enough), 2) students' learning motivation was in the medium category (good enough), and 3) there was a strong relationship between the two the variable with a value of r = 0.661 (with a value of p = 0.000). The conclusion is that the talking stick method has a positive and strong influence on the learning motivation of class VIII students at MTs Nurul Islam Bekasi. To increase students' learning motivation, it is recommended to use a variety of learning methods, one of which is the talking stick method so that students do not feel bored while participating in the learning process. Rendahnya motivasi belajar siswa dapat ditunjukkan dengan kurangnya keaktifan siswa dalam mengikuti pembelajaran. Ketidakaktifan siswa dalam proses pembelajaran dapat meliputi tidak memperhatikan pelajaran, tidak bertanya kepada guru tentang materi yang belum jelas, serta tidak menjawab pertanyaan dari guru. Motivasi belajar merupakan daya penggerak di dalam diri siswa yang menimbulkan kegiatan belajar, yang menjamin kelangsungan dari kegiatan belajar dan yang memberikan arah pada kegiatan belajar sehingga tujuan yang dikehendaki oleh siswa dalam belajar dapat tercapai. Penelitian ini bertujuan untuk mengetahui pengaruh metode talking stick terhadap motivasi belajar siswa kelas VIII MTs Nurul Islam Bekasi. Ukuran sampelnya adalah seluruh siswa kelas VIII MTs Nurul Islam Bekasi yang berjumlah 64 orang. Metode penelitian yang digunakan adalah deskriptif korelasional. Hasil penelitian diperoleh bahwa: 1) penggunaan metode talking stick pada mata pelajaran Akidah Akhlak di MTs Nurul Islam Bekasi cukup efektif (cukup baik), 2) motivasi belajar siswa dalam kategori sedang (cukup baik), dan 3) terdapat hubungan yang kuat antar kedua variabel tersebut dengan nilai r = 0,661 (dengan nilai p = 0,000). Kesimpulannya adalah metode talking stick memiliki pengaruh positif dan kuat terhadap motivasi belajar siswa kelas VIII MTs Nurul Islam Bekasi. Untuk meningkatkan motivasi belajar siswa, disarankan agar menggunakan metode pembelajaran yang bervariasi, salah satunya yaitu metode talking stick agar siswa tidak merasa bosan saat mengikuti proses pembelajaran.